2010
DOI: 10.1111/j.1095-8312.2010.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and distribution routes of the bronze featherback Notopterus notopterus (Osteoglossiformes: Notopteridae) in Indochina

Abstract: Mitochondrial DNA analysis was used to investigate genetic variation in the bronze featherback fish Notopterus notopterus in Indochina. Five hundred and five fish samples collected from 11 localities were separated into three genetically differentiated intraspecific groups. Chao Phraya River samples formed a distinct group. Mekong River samples were clearly separated into two different groups, namely, middle and lower Mekong groups. The lower Mekong group was closely related to Malay Peninsula group, even thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The adult bronze featherbacks have poor swimming abilities and inhabit sluggish water in wetlands and floodplains which may or may not be fed with rivers ( Rainboth, 1996 ) and lay eggs in small clumps on submerged vegetation ( Talwar and Jhingran, 1991 ) and thus are not easily dispersed. Takagi ( Takagi et al, 2006a, 2006b, 2010 ) also observed high genetic differentiation between the populations of N . notopterus from Mekong basin.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The adult bronze featherbacks have poor swimming abilities and inhabit sluggish water in wetlands and floodplains which may or may not be fed with rivers ( Rainboth, 1996 ) and lay eggs in small clumps on submerged vegetation ( Talwar and Jhingran, 1991 ) and thus are not easily dispersed. Takagi ( Takagi et al, 2006a, 2006b, 2010 ) also observed high genetic differentiation between the populations of N . notopterus from Mekong basin.…”
Section: Discussionmentioning
confidence: 90%
“…The ATPase8 and ATPase6 regions of mitochondrial DNA have been successfully analyzed for both phylogeny as well as phylogeography in many fish species ( Chow and Ushiama, 2004; Dammannagoda et al, 2008; Vergara-Chen et al, 2009; Xin-Hong et al, 2004; Yan et al, 2009 ). However, the information on polymorphic molecular markers and their applications is limited to a small part of vast distribution ( Takagi et al, 2006a,b, 2010 ) and genetic relatedness with another notopterid fish, Chitala chitala ( Lal et al, 2006 ). The present study characterized complete sequences of mitochondrial ATPase8 and ATPase6 regions in N .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also used genetic techniques to define appropriate scales for managing wild stocks and have provided important insights to connectivity, movement and life history (Adamson et al, 2009; Biesack et al, 2020; Hurwood et al, 2008; So, van Houdt, & Volckaert, 2006; So et al, 2005). Such studies have revealed signals of historical barriers to gene flow (Takagi et al, 2010), inter‐specific differences in dispersal capabilities (Takagi et al, 2011) and temporal‐based population structure that suggests multiple spawning migrations within a species (So et al, 2005).…”
Section: Overview Of Migratory Fish Knowledge Needs and Relevant Toolsmentioning
confidence: 99%
“…The genetic population structures of Thynnichtys thynnoides, bronze featherback Notopterus notopterus and climbing perch, Anabas testudineus had been examined in the lower Mekong River Basin including several sites around Tonle Sap Lake (Ishikawa et al 2005b;Takagi et al 2010Takagi et al , 2011. Although no genetic differences among sites were detected in T. thynnoides and the bronze featherback, genetic homogeneity among Stung Treng, Lao PDR, Siem Reap and Kampong Chhnang were discovered in the climbing perch (Fig.…”
Section: -1 Fisheries Stock Structure and Data Collection Sites In mentioning
confidence: 99%